A remedy to oxygen limitation problem in antibiotic production: addition of perfluorocarbon - Elibol, M; Mavituna, F (Elsevier Science Sa, 1999)
In this study, the effect of an oxygen carrier, perfluorocarbon, on actinorhodin fermentation by Streptomyces coelicolor A3(2) was investigated using a chemically defined medium in 2 and 201 bioreactors. The inclusion of 50% (v/v) perfluorocarbon in the fermentation medium resulted in a five-fold increase in the maximum antibiotic concentration. The use of perfluorocarbon also caused remarkable increases in both glucose and oxygen consumption rates. Moreover, the increasing concentrations of perfluorocarbon improved the dissolved oxygen profile by raising the minimum dissolved oxygen concentration. It was found that observed increases in the antibiotic production were linearly related to the volumetric oxygen uptake rates. This result could perhaps be attributed to the enhancement of oxygen transfer in S. coelicolor cultures due to the higher oxygen solubilities of the fermentation medium through inclusion of perfluorodecalin. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: actinorhodin; antibiotic; Streptomyces coelicolor; oxygen limitation; perfluorocarbon